Seasonal and Inter-Annual Variations of Carbon Dioxide Fluxes and Their Determinants in an Alpine Meadow - Wang, Song; Chen, Weinan; Fu, Zheng; Li, Zhaolei; Wang, Jinsong; Liao, Jiaqiang; Niu, Shuli (Frontiers in Plant Science, 2022)
Alpine meadow is one of the most important ecosystems on the Qinghai-Tibet Plateau due to its huge carbon storage and wide distribution. Evaluating the carbon fluxes in alpine meadow ecosystems is crucial to understanding the dynamics of carbon storage in high-altitude areas. Here, we investigated the carbon fluxes at seasonal and inter-annual timescales based on five years of observations of eddy covariance fluxes in Zoige alpine meadow on the eastern Tibetan Plateau. We found that Zoige alpine meadow acted as a faint carbon source of 94.69 ± 86.44 g C m−2 yr−1 during the observation periods with large seasonal and interannual variations. At the seasonal scale, gross primary productivity (GPP) and ecosystem respiration (Re) were positively correlated with photosynthetic photon flux density (PPFD), average daily temperature (Ta), vapor pressure (VPD), and had negative relationships with volumetric water content (VWC). Seasonal variations of net ecosystem CO2 exchange (NEE) were mostly explained by Ta, followed by PPFD, VPD, and VWC. The interannual variations (IAV) of GPP and Re were mainly attributable to the IAV of the maximum GPP rate (GPPmax) and maximum Re rate (Remax), respectively, both of which increased with the percentage of Cyperaceae and decreased with the percentage of Polygonaceae changes across years. The IAV of NEE was well explained by the anomalies of maximum CO2 release rate. These results indicated that the annual net CO2 exchange in the alpine meadow ecosystem was controlled mainly by the maximum C release rates. Therefore, a better understanding of physiological response to various environmental factors at peak C uptake and release seasons will largely improve the predictions of GPP, Re and NEE in the context of global change.